Artemisia dracunculus essential oil: phytochemical study, pre-treatment and co-treatment effects on morphine withdrawal syndrome - Zahra Lorigooini; Fatemeh Heibati; Seyyed Matin Ahmadi; Sareh Mohammadi; Mahmoud Rafieian-Kopaei (Brazilian Journal of Pharmaceutical Sciences)
Abstract Drug addiction is one of the most important global problems. Medicinal herbs have been traditionally used in the management and treatment of opioid withdrawal syndrome and pain. The aim of this study was to determine the effect of A. dracunculus essential oil in reducing the symptoms of morphine withdrawal in mice. Male mice (25-30 g) were randomly assigned into 4 groups (n=10). Morphine-dependent groups received morphine (50 and 75 mg/kg ip; three times/day, 3 days) and a single injection of morphine (50 mg/kg) and then naloxone on the fourth day via IP injection. The control group received saline. The post-treated group received morphine for 3 days; on the fourth day, ten minutes before receiving naloxone, A. dracunculus essential oil with a dose of 75 mg/kg was injected. All groups received naloxone 2 hours after receiving the last dose of morphine; then, the morphine withdrawal symptoms were measured for 30 minutes. In the post-treated and co-treated groups, the body stretching and shaking the claw were significantly less than morphine-dependent groups (p<0/05). Also, in the post-treated and co-treated groups, the blinking, itching, and the number of standing on two legs significantly decreased compared to the morphine group. Hence, it might be concluded that A. dracunculus essential oil can significantly reduce morphine withdrawal symptoms.